SEVERE COMPLICATIONS OF A DISK BATTERY INGESTION (CASE REPORT) - Smaranda Diaconescu; Nicoleta Gimiga; Claudia Olaru; Valeriu V. Lupu; Iulia Straticiuc-Ciongradi; S.G. Aprodu; Anamaria Ciubara; Marin Burlea (Amaltea Medical Publishing House, 2014)
Certain categories of foreign bodys ingestion in children can cause dangerous and severe complications leading to increased morbidity rates among them. We report a case of disk battery ingestion in a 2 year old girl, with impaction in the upper cervical esophagus, extracted in otolaryngology service but complicated afterwards with tracheo-oesophageal fi stula and aspiration pneumonia and by long-term effect with high esophageal stenosis that required endoscopic dilatation.